EKONOMI KREATIF SEBAGAI POTENSI EKONOMI KOTA PADANG PANJANG DI MASA NEW NORMAL - Primadini, Rindy; Arrazy, Masruqi (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
Padang Panjang Municipality’s economy experienced an economic contraction in 2020 due to the Covid-19 pandemic. Tourism as the mainstay of this city has become one of the economic activities that has decreased significantly. The situation that has not been normal until now requires identifying sectors that have the potential to face the new normal period. This research uses secondary data with the Shift-Share method as an analytical tool. The data used is the Gross Regional Domestic Product (GRDP) of Padang Panjang and West Sumatra Province with the data period of 2019 and 2020. From the results of the analysis, it is known that none of the sectors that support tourism are the leading sectors. Sectors that can be featured include the Education Services Sector and the Trade Sector. This sector is part of the Creative Economy so that this activity can be a potential that can be developed.